PENGARUH SALAT DUHA TERHADAP KETENANGAN JIWA PADA MAHASISWA TINGKAT AKHIR (Studi Kasus Mahasiswa Program Beasiswa Santri Berprestasi Angkatan 2015 Universitas Islam Negeri Sunan Gunung Djati Bandung) - Rahmatullah Rahmatullah; Muhtar Gojali; Naan Naan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
Students of Achievement Santri Scholarship Program which is then abbreviated as PBSB is a student who gets a scholarship in the form of funding during the education process both in the form of college funding and providing assistance for daily life. According to the researchers' assumptions, PBSB students are more prone to anxiety than other students because they are burdened with demands to graduate on time by the state. This study aims to determine the intensity of the implementation of the students 'prayer, to know the condition of students' peace of mind, and the effect of the implementation of the prayer of the students on the peace of mind of the 2015 PBSB students of Sunan Gunung Djati State Islamic University, Bandung. The purpose of the holding of this research is expected to be able to add new insights in the development of Sufistic spiritual psychotherapy, as a new reference for the world of psychotherapy regarding the improvement of mental tranquility through duha prayer. Duha prayer is one of the sunnah prayers whose implementation starts when the sun rises until the noon time has arrived. The minimum number of rakaat duha prayers is two rak'ahs and the most they can (Yazid, 2014). While people who are calm souls are people who have regularity and harmony in the functions of their souls, able to solve various problems of living with a person who has confidence, courage in undergoing life's challenges and can adjust to their environment (Zakiah, 1982). The method that I use in this research is a quantitative method with correlative study design. The process of collecting data in this study is by distributing questionnaires (questionnaire) online to the respondents. The data that has been obtained is then processed into numbers through the IBM SPSS Statistics 24 application. After going through the process of analyzing data obtained by the author in the field, it can be revealed that: 1) The intensity of the implementation of the Duha Prayer for 2015 PBSB students of UIN Sunan Gunung Djati Bandung is 73% of the criteria determined in the study. 2) The peace of mind of PBSB UIN Sunan Gunung Djati Bandung students reached 73% of the categories determined by the author in the study. 3) Duha prayer has a good influence on the peace of mind of the 2015 PBSB students of UIN Sunan Gunung Djati Bandung, reaching 50.2%, while the rest is influenced by other aspects outside the study. This research data shows that; the better the intensity of the implementation of the duha prayer the more calm the student's soul is, and the worse the intensity of the implementation of the duha student prayer the more uneasy the student's soul.